809. Modified Laboratory Reporting to Prevent Catheter-Associated Urinary Tract Infections (CAUTIs). (31st December 2020) - Monsalud, Cherie Faith; Singh, Kamaljit; McElvania, Erin; Schora, Donna; Grant, Jennifer; Lavin, Mary Alice; Lim, Rachel; Zelencik, Shane
Abstract: Background: Catheter-associated urinary tract infections (CAUTIs) are among the most common healthcare-associated infections. Many patients at our institution with a CAUTI do not have signs or symptoms of infection and bacterial growth likely represents asymptomatic bacteriuria (ASB). As a result, we implemented a Modified Lab Workflow (MLW) focused on diagnostic stewardship to improve urine culture (UCx) reporting and prevent misclassification and unnecessary treatment of CAUTIs. Methods: On Sep. 1, 2019, laboratory reporting of Foley UCx was modified according to the protocol in Figure 1. UCx results were divided into 3 groups: (1) no growth, (2) mixed bacterial flora (≥3 organisms) not consistent with infection or (3) growth of ≤2 organisms with at least 1 organism ≥10 5 cfu/ml per National Healthcare Safety Network (NSHN) CAUTI definition. Group 3 UCx were resulted with instructions to the clinician (see Figure 1.). When requested, group 3 results were reviewed by Infection Prevention and released with organism identification and antibiotic susceptibility if it met Infectious Diseases Society of America (IDSA) CAUTI criteria. Otherwise they were resulted as: "Bacterial growth indicative of contamination or colonization." Figure 1. Modified Laboratory Workflow for Reporting Urine Cultures from Foley Catheters Results: Between Sep. 1, 2019 to Mar. 1, 2020, a total of 134 UCx from catheterized patients were reviewed. Forty-two (31%) of UCx were from patients with a Foley in-situ ≥48 hours and processed through MLW; 92 UCx were from a Foley in place < 48 hours and excluded from the study. Of the 42 UCx processed via MLW, 16 (38%) were no growth and 7 (17%) had bacterial growth suggestive of contamination. For group 3, 19/42 (45%) had growth of significant bacteria but only 1(5%) met IDSA criteria for reporting. During the study, 6 additional CAUTIs were reported due to incorrect specimen labeling causing Foley urine specimens to subvert MLW. Conclusion: During our study, we identified 1 CAUTI through apt MLW use. Seven total CAUTIs occurred (SIR=0.66); a majority due to incorrect UCx source labeling, resulting in missed MLW screening. Ten CAUTIs (SIR=0.97) were reported in the preceding 6 months. As part of a comprehensive CAUTI prevention program, a MLW can help reduce classification of ASB as a CAUTI. Education to providers on precise labeling of UCx source is a key component of a successful MLW. Disclosures: All Authors : No reported disclosures